Off-line Arabic (Indian) numbers recognition using expert system - Malallah, Fahad Layth; Saeed, Mostafah Ghanem; M. Aziz, Maysoon; Arigbabu, Olasimbo Ayodeji; Syed Ahmad, Sharifah Mumtazah (The Science and Information Organization, 2016)
This paper proposes an effective approach to automatic recognition of printed Arabic numerals which are extracted from digital images. First, the input image is normalized and pre-processed to an acceptable form. From the preprocessed image, components of the words are segmented into individual objects representing different numbers. Second, the numerical recognition is performed using an expert system based on a set of if-else rules, where each set of rules represents the categorization of each number. Finally, rigorous experiments are carried out on 226 random Arabic numerals selected from 40 images of Iraqi car plate numbers. The proposed method attained an accuracy of 97%.